Bahasa Inggris: Bahasa Inggris - mujiyana, mujiyana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study examines the ethical application in investigating sexual abuse cases where minors are the perpetrators. Recognizing children as a vulnerable group, it emphasizes the importance of upholding their rights—such as fair treatment and protection from psychological harm—throughout the legal process. Ethical practices in investigation include ensuring communication is appropriate for a child’s cognitive level and avoiding intimidation or coercion. The research highlights the critical role of investigators in creating a safe environment, yet finds that ethical principles are frequently overlooked. Time pressures and the sensitivity of molestation cases often lead to procedural shortcuts that jeopardize children's rights. These issues are compounded by a lack of specialized training and limited psychosocial support for minors involved in such cases. To address these challenges, the study recommends enhancing investigator training in child psychology and trauma-informed approaches. It also calls for greater collaboration between government and non-governmental organizations to provide accessible psychosocial services. By improving professional competencies and support systems, the study argues that ethical, child-centered investigations can be more consistently applied—ensuring that the legal process safeguards both the rights and well-being of minors